Behavioral manipulation of Drosophila suzukii for pest control: high attraction to yeast enhances insecticide efficacy when applied on leaves. Issue 3 (17th November 2021) - Rehermann, Guillermo; Spitaler, Urban; Sahle, Karolina; Cossu, Carlo S; Donne, Lorenz Delle; Bianchi, Flavia; Eisenstecken, Daniela; Angeli, Sergio; Schmidt, Silvia; Becher, Paul G
Abstract: BACKGROUND: The invasive pest, Drosophila suzukii attacks fresh soft‐skinned fruit. Broad‐spectrum insecticides are implemented for control but there is a need to reduce environmental risks and insecticide residues on fruits. Hanseniaspora uvarum is a yeast frequently found on ripe fruits and associated with D. suzukii . We aim to exploit the ecological association and attraction of D. suzukii to H. uvarum by developing an attract‐and‐kill strategy, with spray‐application on canopy but not fruit. We therefore investigated D. suzukii attraction, egg‐laying and mortality when exposed to insecticidal yeast‐based formulations. RESULTS: Hanseniaspora uvarum strongly attracted D. suzukii when applied on leaves of grapevine, Vitis vinifera . Notably, this attractiveness was competitive to ripe grape berries that were susceptible to D. suzukii infestation. Moreover, adding H. uvarum enhanced the efficacy of insecticidal formulations against D. suzukii . Flies exposed to leaves treated with yeast‐insecticide formulations showed higher mortality and laid a lower number of eggs compared to flies exposed to insecticide alone. In a wind tunnel, all treatments containing H. uvarum alone or in combination with insecticides, caused similar upwind flight and landing at the odor source, which provides evidence that the addition of insecticide did not reduce D. suzukii attraction to yeast. CONCLUSION: Hanseniaspora uvarum can be used to manipulate the behavior of D. suzukii by attracting flies to insecticide formulations. Yeast attraction is competitive to grape berries and improves insecticide effectiveness, suggesting that sprays covering canopy only, could reduce residues on fruit without compromising management efficacy. Abstract : Hanseniaspora uvarum yeast lured Drosophila suzukii to grapevine leaves and decreased attraction to fruit. Hanseniaspora uvarum ‐insecticide formulations are attractive and effective. Targeted canopy sprays might reduce residues on fruit. © 2021 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.